2009
DOI: 10.1002/esp.1879
|View full text |Cite
|
Sign up to set email alerts
|

Application of boat‐based laser scanning for river survey

Abstract: The boat-based, mobile mapping system (BoMMS) with a laser scanner allows the derivation of detailed riverine topographical data for fl uvial applications. Combined with data acquisition from static terrestrial LiDAR (light detection and range) or mobile terrestrial LiDAR on the ground, boat-based laser scanning enables a totally new fi eld mapping approach for fl uvial studies. The BoMMS approach is an extremely rapid methodology for surveying riverine topography, taking only 85 min to survey a reach approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
102
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 29 publications
0
102
0
1
Order By: Relevance
“…Over the last decade, terrestrial laser scanners proved capable of generating very high quality DEM data (e.g. Heritage and Hetherington, 2007;Alho et al, 2009;Hodge et al, 2009a,b;Schaefer and Inkpen, 2010) and have almost become routine in some DEM collection strategies. However, they remain relatively expensive items of technology and have only recently become truly portable.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, terrestrial laser scanners proved capable of generating very high quality DEM data (e.g. Heritage and Hetherington, 2007;Alho et al, 2009;Hodge et al, 2009a,b;Schaefer and Inkpen, 2010) and have almost become routine in some DEM collection strategies. However, they remain relatively expensive items of technology and have only recently become truly portable.…”
Section: Introductionmentioning
confidence: 99%
“…After the integration of a scanning mechanism with lidar and an inertial measurements unit with GPS in the early 1990s, it has been possible to use first airborne laser scanning (ALS), then MLS data, in addition to static based terrestrial laser scanning (TLS), to improve the measurement and modeling of fluvial environments (e.g., [2][3][4][5][6][7][8][9][10][11][12]). High-resolution ALS provides detailed information on topographical features of fluvial environments that influence the river hydraulics, giving, therefore, the potential to improve existing hydraulic models (e.g., [13][14][15][16][17]).…”
Section: Introductionmentioning
confidence: 99%
“…The improved topographical data allows for better planning of the management of river hydraulics and erosion control (e.g., [14,18]) and better analysis of different flooding scenarios [16]. Alho et al [11,19] showed that MLS offered a very effective method for surveying riverine topography compared to traditional TLS. In that study, 6 km of riverine topography was surveyed by the boat-mounted mobile laser scanner within 85 min, whereas TLS measurements of the point bars of the same area took over 8 hours.…”
Section: Introductionmentioning
confidence: 99%
“…This limited our useful scan radius to approximately 50 m. Our implementation of TLS afforded sufficient mapping extent to address the questions of our study, but would not be suitable for larger mapping projects. Some researchers have extended the useful range of scans by elevating the scanner to considerable heights above the sediment surface, e.g., [24], and recently, by developing mobile TLS platforms, e.g., [43].…”
Section: Effectiveness Of Tlsmentioning
confidence: 99%